2006
DOI: 10.1073/pnas.0511321103
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by pharmacologic blockade of the GAPDH death cascade

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) participates in a cell death cascade wherein a variety of stimuli activate nitric oxide (NO) synthases with NO nitrosylating GAPDH, conferring on it the ability to bind to Siah, an E3-ubiquitin-ligase, whose nuclear localization signal enables the GAPDH͞Siah protein complex to translocate to the nucleus where degradation of Siah targets elicits cell death. R-(؊)-Deprenyl (deprenyl) ameliorates the progression of disability in early Parkinson's disease and also h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
200
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 224 publications
(212 citation statements)
references
References 29 publications
5
200
1
1
Order By: Relevance
“…Recent studies showed that S-nitrosylation of GAPDH can mediate the translocation of GAPDH-Siah1 protein complex to the nucleus and initiates apoptosis (29,30). Our findings that S-nitrosylation of XIAP can affect its antiapoptotic function further suggest that nitrosative stress can affect the survival of neurons through targeting a number of pathways.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent studies showed that S-nitrosylation of GAPDH can mediate the translocation of GAPDH-Siah1 protein complex to the nucleus and initiates apoptosis (29,30). Our findings that S-nitrosylation of XIAP can affect its antiapoptotic function further suggest that nitrosative stress can affect the survival of neurons through targeting a number of pathways.…”
Section: Discussionmentioning
confidence: 69%
“…Apart from impairing neuroprotection proteins, S-nitrosylation is also involved in mediating cell death through GAPDH (28,29). Recent studies showed that S-nitrosylation of GAPDH can mediate the translocation of GAPDH-Siah1 protein complex to the nucleus and initiates apoptosis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…R-(-)-deprenyl (Selegiline), which may ameliorate the progression of early stage PD, appears to prevent S-nitrosylation of GAPDH both in cellular and animal models of PD. 106 Initially, the effects of Deprenyl were thought to depend on inhibition of monoamine oxidase-B (MAO-B); however, recent research has suggested that Deprenyl increases survival of dopaminergic neurons independently of MAO-B inhibition, and GAPDH represents a possible target for the beneficial effect of Deprenyl. 107 It is postulated that the binding of Deprenyl to GAPDH interferes with the formation of SNO-GAPDH and its interaction with Siah1, thereby affording neuroprotection.…”
Section: S-nitrosylation As a Potential Positive Regulator Of Excitotmentioning
confidence: 99%
“…We further explored this relationship using the pharmacologic drug deprenyl, which is a small molecule inhibitor that binds tightly to GAPDH and prevents its S-nitrosylation at Cys152 (23). Heme insertion into iNOS became resistant to NO inhibition in cells given deprenyl (Fig.…”
Section: Cellular Heme Insertion Into Inos Involves Gapdh and Is Regula-mentioning
confidence: 99%